1999
DOI: 10.1002/(sici)1097-4598(199902)22:2<156::aid-mus3>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing myopathy induced by overexpression of interferon-? in transgenic mice

Abstract: A transgenic mouse model has been established in which the cytokine interferon‐γ (IFN‐γ) is overexpressed through the action of the acetylcholine receptor epsilon promoter acting at the neuromuscular junction. While originally developed as a model for the study of the pathogenesis of myasthenia gravis, there are important differences from both human myasthenia gravis and its animal model, experimental autoimmune myasthenia gravis. By 4 months of age there was a well‐established inflammatory, predominantly necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
1
17
0
1
Order By: Relevance
“…However, IFN-␥ signaling is likely to be tightly regulated, as negative effects of IFN-␥ have been observed as well. When IFN-␥ is overexpressed at the neuromuscular junction in transgenic mice, the mice demonstrate an age-dependent necrotizing myopathy (51). When cultured myoblasts were stimulated with exogenous IFN-␥, the proliferation of myoblasts and the fusion into myotubes were inhibited (21,57).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…However, IFN-␥ signaling is likely to be tightly regulated, as negative effects of IFN-␥ have been observed as well. When IFN-␥ is overexpressed at the neuromuscular junction in transgenic mice, the mice demonstrate an age-dependent necrotizing myopathy (51). When cultured myoblasts were stimulated with exogenous IFN-␥, the proliferation of myoblasts and the fusion into myotubes were inhibited (21,57).…”
supporting
confidence: 63%
“…While IFN-␥ is required for efficient muscle repair, constitutive expression causes necrotizing myopathies (51). We believe the data presented here support both of these roles.…”
Section: Discussionmentioning
confidence: 99%
“…endothelial cells to produce various inflammatory cytokines, chemokines, and adhesion molecules. Moreover, these cytokines might have myocytotoxic effects (42)(43)(44). Our results showed that the majority of the F4/80 ϩ macrophages expressed CX3CR1 in the muscle of EAM mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, MBP-IFN-␥ transgenic mice were not reported to have cerebral calcification (64,65). On the other hand, prominent calcification of muscle tissue occurred in transgenic mice with expression of IFN-␥ targeted to the neuromuscular junction (66). The basis for the differences between these transgenic models in terms of calcification is puzzling.…”
Section: Discussionmentioning
confidence: 99%